Analysis of The Role of Academic Papers in The Application of The Concept of Meaningful Community Participation in Law No. 13 of 2022 Concerning The Second Amendment to Law No. 12 of 2011 Concerning the Formulation of Legislation - Mardiana, Mardiana; Rahmadina, Adji Annisa; Ramadoni, Sofwan Rizko (Jurnal Hukum dan Keadilan, 2025)
This study examines the existence of academic manuscripts in implementing the concept of meaningful public participation as mandated by Law No. 13 of 2022 concerning the Second Amendment to Law No. 12 of 2011 on the Establishment of Laws and Regulations. The main issue addressed is the weak consistency in attaching academic manuscripts to the legislative process, which often renders public participation merely formal and not substantive. The objective of this research is to analyze the urgency of academic manuscripts in ensuring justice, inclusivity, and transparency in law-making, while also evaluating their practical application in drafting Regional Regulations (Perda) in Bontang City during 2018–2024. The research applies a normative legal method (doctrinal research) using statutory, conceptual, and case approaches. The data analyzed consist of primary and secondary legal materials as well as empirical evidence from Bontang City’s e-archive. The findings reveal that academic manuscripts play a strategic role in strengthening public participation; however, in practice, they are often disregarded or prepared only as administrative formality without substantive study. The Bontang case study demonstrates the low consistency of academic manuscripts in the drafting of local regulations, leading to weak legitimacy and regulatory quality. This study concludes that the existence of academic manuscripts must be reinforced through stricter regulation and inclusive legislative practices. The recommendations emphasize the need for a stronger mechanism of public information disclosure, mandatory substantive participation, and institutional capacity building to ensure that every policy enacted is based on scientific analysis and genuinely reflects the aspirations of the people.